Preparation of spherical and flaky CrF3-3H2O micro-nano powder and crystalline state transformation method of spherical and flaky CrF3-3H2O micro-nano powder

The uniform morphology of CrF3·3H2O micro-nano powder was prepared by hydrofluoric acid reaction, and the crystalline transformation was achieved through heat treatment, which solved the problems of CrF3·3H2O micro-nano powder preparation and crystalline control in the prior art, and improved the material The performance and application potential are suitable for high-performance coatings and catalysts.

CN119176581AActive Publication Date: 2024-12-24LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202411449857.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-24
Estimated Expiration
2044-10-17

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of spherical and flaky CrF3. 3H2O micro-nano powder and a crystalline state transformation method of the spherical and flaky CrF3. 3H2O micro-nano powder. An HF acid solution is slowly added into the Cr2AlB2 powder, and the mixture is stirred to react for 4-20 h at the temperature of 25-40 DEG C; the mass fraction of the HF acid solution is 20-45%; after the reaction is finished, centrifugally washing the obtained solution with deionized water and absolute ethyl alcohol in sequence until the solution is neutral; and carrying out freeze drying on the obtained precipitate to obtain spherical CrF3. 3H2O powder, and carrying out ultrasonic treatment in an ethanol solution to fully expand the spherical CrF3. 3H2O powder so as to form a two-dimensional sheet material. The spherical CrF3. 3H2O micro-nano powder is prepared on the basis of selective etching reaction of hydrofluoric acid to Cr2AlB2, the CrF3. 3H2O micro-nano powder which is uniform in morphology and narrow in particle size distribution can be obtained by adjusting reaction conditions, and crystalline state conversion of CrF3. 3H2O is achieved through heat treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and in particular relates to a preparation method of spherical and flaky CrF3·3H2O micro-nano powders and a crystalline transformation method thereof. Background Art

[0002] With the rapid development of modern science and technology, the research and development of new materials has played a key role in promoting the progress of many fields such as industry, electronics, and energy. Among them, transition metal fluorides have become a research hotspot in the field of materials science due to their unique physical and chemical properties, such as high electronegativity, high ionic conductivity, excellent thermal stability and chemical stability. Transition metal fluorides have shown broad application prospects in batteries, capacitors, magnetic materials, catalysts, and anti-corrosion coatings. CrF3·3H2O, as an important chromium-based fluoride, has a molecular structure of chromium fluoride trihydrate and has potential application value in catalytic reactions, magnetic materials, and anti-corrosion coatings. However, the conventional methods for preparing CrF3·3H2O micro-nano powders currently have some shortcomings, such as complex preparation process, harsh reaction conditions, uneven product morphology, and wide particle size distribution, which limits its widespread promotion in high-performance material applications.

[0003] The existing preparation methods of CrF3·3H2O mainly include solution chemistry, sol-gel, coprecipitation and solid phase reaction. Although these methods can prepare CrF3·3H2O powder, it is often difficult to obtain micro-nano powders with uniform morphology and controllable size due to the complexity of reaction conditions and the difficulty of controlling the morphology. At the same time, these methods usually require a long reaction process, which not only increases energy consumption, but also easily leads to crystal defects of the material, thereby affecting its performance in practical applications. In addition, although polycrystalline CrF3·3H2O performs well in some applications, amorphous materials often have better performance in some specific fields, such as magnetic materials and catalysts. Amorphous materials usually have higher surface area, more uniform distribution of active sites and better corrosion resistance due to their lack of long-range ordered atomic arrangement. Therefore, a simple and effective process was developed to not only prepare CrF3·3H2O micro-nano powders with uniform morphology, but also achieve its crystalline transformation through heat treatment.

[0004] The existing technology still has certain limitations and challenges in the preparation of CrF3·3H2O micro-nano powders and their morphology and crystal state. Developing a simple and efficient preparation method that can achieve the crystal state transformation of the material by controlling the heat treatment conditions will provide new ideas and technical support for the research and application of new functional materials. Summary of the invention

[0005] The present invention provides a method for preparing CrF3·3H2O micro-nano powder and a method for regulating its crystal state, and also obtains CrF3·3H2O spherical or flaky powder with micro-nano structure, and corresponding amorphous CrF3 powder and crystalline Cr2O 2.4 With Cr2O3 powder: This material is suitable for the development of high-performance coating materials, lubricants, catalysts and other functional materials.

[0006] 1. Preparation of spherical CrF3·3H2O micro-nano powder The present invention provides a method for preparing spherical CrF3·3H2O micro-nano powder by reacting Cr2AlB2 with hydrofluoric acid. The specific method is as follows: (1) Slowly add HF acid solution to Cr2AlB2 powder, and stir at 25-40 °C and 100-350 r / min for 4-20 h; the mass fraction of the HF acid solution is 20-45%.

[0007] The particle size of Cr2AlB2 powder is controlled below 50 microns. The concentration of Cr2AlB2 powder in HF acid solution is 0.04~0.1g / mL.

[0008] (2) After the reaction is completed, the obtained solution is centrifuged and washed with deionized water and anhydrous ethanol successively until it becomes neutral; the centrifugal speed is 3000-5000 r / min.

[0009] (3) The obtained precipitate is freeze-dried at -60°C to -80°C to obtain spherical CrF3·3H2O powder.

[0010] 2. Preparation method of two-dimensional flake CrF3·3H2O The spherical CrF3·3H2O micro-nano powder was ultrasonically treated in an ethanol solution to fully expand it to form a two-dimensional flaky CrF3·3H2O micro-nano powder material.

[0011] 3. Crystalline transformation method of CrF3·3H2O micro-nano powder 1. Heat-treat spherical or two-dimensional flaky CrF3·3H2O micro-nano powder at a temperature of 160-300°C for more than 30 minutes to remove crystal water and obtain amorphous spherical or flaky CrF3 powder.

[0012] 2. Heat treatment of spherical or two-dimensional flaky CrF3·3H2O nanopowders in an oxygen-deficient environment at a temperature of 400°C to 1000°C for more than 30 minutes to form Cr2O 2.4 Spherical or flake materials; The spherical or two-dimensional flaky CrF3·3H2O micro-nano powder is heat-treated in an atmospheric environment at a temperature of 400°C to 1000°C for a time greater than 30 minutes to form a flaky material of Cr2O3 with oxygen vacancies.

[0013] The change from spherical to flake can be completed first, and then the amorphous state can be transformed, or the crystalline state can be completed first, and then the spherical to flake material can be transformed. The process of completing the crystalline state first and then the spherical to flake material transformation is as follows: 1. Crystalline transformation method of spherical CrF3·3H2O micro-nano powder (1) A method for transforming spherical CrF3·3H2O micro-nano powder from a polycrystalline state to an amorphous state by heat treatment, the specific steps comprising: The prepared spherical CrF3·3H2O micro-nano powder is heat-treated at a temperature of 160-300°C to remove crystal water and obtain amorphous CrF3 powder; the heat treatment time is greater than 30 minutes.

[0014] (2) Spherical CrF3·3H2O nanopowders are transformed into polycrystalline Cr2O3 or Cr2O 2.4 The prepared spherical CrF3·3H2O nanopowder is heat treated in an oxygen-deficient environment or an atmospheric environment at a temperature of 400°C to 1000°C to form Cr2O with oxygen vacancies. 2.4 Or Cr2O3; heat treatment time is greater than 30 minutes.

[0015] 2. Preparation method of two-dimensional flake CrF3·3H2O The prepared spherical crystalline CrF3·3H2O micro-nano powder or amorphous CrF3 powder is ultrasonically treated in an ethanol solution to fully expand it to form a two-dimensional flaky CrF3·3H2O micro-nano powder material or a two-dimensional flaky amorphous CrF3 powder material.

[0016] 4. Preparation of spherical CrF3·3H2O micro-nano powder and its crystal transformation mechanism The preparation of CrF3·3H2O micro-nano powder is mainly based on the selective etching reaction of Cr2AlB2 by hydrofluoric acid (HF). Cr2AlB2 is a composite material of transition metal carbides and borides with a layered structure. In its structure, there are strong chemical bonds between chromium atoms and aluminum and boron atoms, and the stability of these bonds is different in acidic media. During the reaction, HF reacts chemically with aluminum and chromium in Cr2AlB2 to generate chromium fluoride and other by-products. The specific reaction steps can be summarized as follows: 1. HF first attacks the aluminum in Cr2AlB2 to generate AlF3 and H2; 2. As the reaction proceeds, the chromium in Cr2AlB2 is gradually converted into CrF3 and combines with water molecules in the solution to generate CrF3·3H2O. By controlling the reaction conditions (acid concentration, reaction temperature and time, drying temperature, etc.), the crystallization process of CrF3·3H2O can be adjusted to gradually form a spherical micro-nano powder structure. The formation of the spherical morphology is mainly related to the surface tension in the solution and the growth dynamics of the particles. Under appropriate conditions, the particles of CrF3·3H2O gradually form spherical micro-nano structures through a uniform nucleation and growth process. By adjusting the reaction conditions, CrF3·3H2O micro-nano powders with uniform morphology and narrow particle size distribution can be obtained.

[0017] The crystalline transformation process of CrF3·3H2O is achieved through heat treatment. The core of heat treatment is to transform the material from polycrystalline to amorphous by controlling the temperature and holding time. Its mechanism can be divided into the following aspects: 1. Lattice perturbation during heating: During the heating process, the lattice of CrF3·3H2O absorbs thermal energy, resulting in intensified vibration of the lattice. When the heating temperature reaches a certain level, the atomic positions in the lattice begin to become unstable and gradually lose their long-range order. This disorder of atomic arrangement is the main reason for the formation of amorphous state; 2. The role of surface energy and internal stress: At the micro-nano scale, CrF3·3H2O powder has a large specific surface area, which makes the surface energy have a significant effect on the thermodynamic behavior of the material. As the temperature increases, the energy difference between the inside and the surface of the powder is further intensified, causing an increase in the internal stress of the material. This internal stress promotes the collapse of the crystal structure, which in turn causes the material to transform from an ordered polycrystalline state to a disordered amorphous state. 3. Removal of water molecules: At higher temperatures, the crystal water in CrF3·3H2O may be partially or completely removed, and this process will also cause further destruction of the crystal lattice. The removal of crystal water not only changes the stability of the crystal structure, but may also lead to the formation of voids or defects inside the crystal, which provide conditions for the occurrence of amorphization. As the temperature rises further, the residual fluoride continues to decompose, the oxidation process intensifies, and the lattice is ordered under high temperature conditions to gradually form Cr2O 2.4 And chromium oxide Cr2O3.

[0018] The present invention provides a new method for preparing spherical CrF3·3H2O micro-nano powder based on the selective etching reaction of Cr2AlB2 with hydrofluoric acid (HF). By adjusting the reaction conditions, spherical CrF3·3H2O micro-nano powder with uniform morphology and narrow particle size distribution can be obtained, and it can be easily converted into a two-dimensional flaky material, and the crystalline transformation of CrF3·3H2O can be achieved by heat treatment. The spherical or lamellar structure can increase the specific surface area of ​​the material, which helps to improve the reaction activity in catalytic or electrode materials. In addition, the spherical particles with uniform morphology have better fluidity and are easy to disperse evenly, which is suitable for processing processes such as coating or 3D printing. The two-dimensional lamellar material exhibits excellent lubrication properties in tribological applications, reduces the friction coefficient, and prolongs the service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the X-ray diffraction pattern of the CrF3·3H2O powder prepared in Example 1 of the present invention.

[0020] Figure 2 This is a scanning electron microscope image of the spherical CrF3·3H2O powder in Example 1 of the present invention.

[0021] Figure 3 This is the XRD diagram of the amorphous CrF3 powder after amorphization in Example 3 of the present invention.

[0022] Figure 4 This is a TEM image of the amorphous CrF3 powder after amorphization in Example 3 of the present invention.

[0023] Figure 5 This is a TEM image of the lamellar amorphous CrF3 powder after ultrasonic treatment in Example 4 of the present invention.

[0024] Figure 6 1 is the XRD diagram of the powder after high temperature heat treatment in Examples 5 and 6 of the present invention. DETAILED DESCRIPTION

[0025] The present invention is further explained below with reference to specific embodiments.

[0026] Example 1 (1) Weigh 5 g of Cr2AlB2 powder, put it into an agate mortar, grind and sieve it, and control the particle size to be less than 50 μm; (2) Transfer the ground powder into a polytetrafluoroethylene beaker, measure 100 ml of 20% HF acid solution, and slowly pour it into the beaker; (3) At 25 °C, the speed of the magnetic stirrer was set to 350 r / min and the reaction duration was set to 4 h. (4) After the reaction, the mixture was washed at least three times by centrifugation at 3000 r / min with deionized water, then washed with anhydrous ethanol until the pH value was close to 7, and finally freeze-dried at -60 °C for 8 h to obtain spherical CrF3·3H2O powder; The crystallinity test was carried out using an X-ray diffractometer. Figure 1 The results show that the CrF3·3H2O powder has a good crystal phase. The morphology of the powder was observed using a scanning electron microscope. Figure 2 The uniform spherical structure and particle size distribution show that the material has a uniform morphology and a narrow particle size distribution. The morphology of the material significantly affects its performance and application. The spherical or lamellar structure can increase the specific surface area of ​​the material, which helps to improve the reaction activity in catalytic or electrode materials. In addition, spherical particles have better fluidity and are easy to disperse evenly, making them suitable for processing such as coating or 3D printing.

[0027] (5) The spherical CrF3·3H2O powder was ultrasonically treated for 20 min to obtain an unfolded lamellar CrF3·3H2O material. The two-dimensional lamellar material exhibits excellent lubrication properties in tribological applications, reduces the friction coefficient, and prolongs the service life. Morphology optimization can simultaneously enhance the mechanical strength and electrical and thermal conductivity of the material, making it suitable for a wide range of high-performance application scenarios.

[0028] Example 2 (1) Weigh 5 g of Cr2AlB2 powder, put it into an agate mortar, grind and sieve it, and control the particle size to be less than 50 μm; (2) Place the ground powder into a polytetrafluoroethylene beaker, measure 100 ml of 40% HF acid solution, and slowly pour it into the beaker; (3) Set the reaction temperature to 40 °C, the speed of the magnetic stirrer to 100 r / min, and the reaction time to 4 h; (4) After the reaction, the mixture was washed at least three times by centrifugation at 3000 r / min with deionized water, then washed with anhydrous ethanol until the pH value was close to 7, and finally freeze-dried at -60°C for 8 hours to obtain spherical CrF3·3H2O powder. The X-ray diffraction test was performed, and the results were consistent with those in Example 1.

[0029] Example 3 (1) Take the spherical CrF3·3H2O powder prepared in Example 1; (2) Place the powder in a vacuum tube furnace and perform heat treatment under a protective atmosphere (argon); set the furnace temperature to 180°C and the holding time to 4 hours; (3) After heat treatment, the sample is naturally cooled to room temperature in the furnace to avoid sample damage caused by thermal shock, thereby obtaining amorphous CrF3 powder.

[0030] X-ray diffraction analysis was performed to confirm the transition from the polycrystalline state to the amorphous state. Figure 3 The results show that the characteristic peaks of the powder crystals after heat treatment weakened, showing an amorphous trend. The morphology of the powder after heat treatment was analyzed using a transmission electron microscope. Figure 4 Features of an amorphous structure were observed.

[0031] Example 4 (1) Take the spherical CrF3·3H2O powder prepared in Example 2; (2) placing the powder in a vacuum tube furnace and setting it for heat treatment in a vacuum environment; setting the furnace temperature to 250°C and the holding time to 6 hours; (3) After the heat treatment is completed, the sample is naturally cooled to room temperature in a vacuum to obtain spherical amorphous CrF3 powder.

[0032] (4) The spherical amorphous CrF3 powder is subjected to ultrasonic treatment for 20 min to obtain an expanded lamellar amorphous CrF3 powder material.

[0033] Figure 5 The spherical unfolded sheet morphology after ultrasonic treatment can be seen, and the structural characterization is consistent with that of Example 3.

[0034] Example 5 (1) Take the spherical CrF3·3H2O powder prepared in Example 2; (2) Place the powder in a vacuum tube furnace and perform heat treatment in a vacuum environment. Set the furnace temperature to 800°C and the holding time to 2 hours.

[0035] (3) After the heat treatment is completed, the sample is allowed to cool naturally to room temperature in a vacuum.

[0036] X-ray diffraction test results show that the main substance after heat treatment at 800℃ in vacuum environment is Cr2O containing oxygen vacancies. 2.4 , and the characteristic peaks of powder crystallization are obvious (such as Figure 6 (Left)).

[0037] Example 6 The heat treatment under vacuum in Example 5 was replaced by heat treatment under atmospheric conditions, and the rest was the same as in Example 5, to obtain Cr2O3 containing oxygen vacancies. X-ray diffraction test was performed, and the results showed that the main substance after heat treatment at 800°C under atmospheric conditions was Cr2O3 containing oxygen vacancies, and the characteristic peaks of powder crystallization were obvious (such as Figure 6 (right)).

Claims

1. A method for preparing spherical CrF3·3H2O micro-nano powder, characterized in that: Slowly add HF acid solution to Cr2AlB2 powder, and stir the reaction at 25-40 °C for 4-20 h; the mass fraction of the HF acid solution is 20-45%; after the reaction, the obtained solution is centrifugally washed with deionized water and anhydrous ethanol successively until neutral; the obtained precipitate is dried to obtain spherical CrF3·3H2O powder.

2. The method for preparing spherical CrF3·3H2O micro-nano powder according to claim 1, characterized in that: The particle size of the Cr2AlB2 powder is controlled to be below 50 microns.

3. The method for preparing spherical CrF3·3H2O micro-nano powder according to claim 1, characterized in that: The concentration of the Cr2AlB2 powder in the HF acid solution is 0.04-0.1 g / mL.

4. The method for preparing spherical CrF3·3H2O micro-nano powder according to claim 1, characterized in that: The stirring speed is 100-350 r / min; the centrifugal speed is 3000-5000 r / min.

5. The method for preparing spherical CrF3·3H2O micro-nano powder according to claim 1, characterized in that: Freeze drying is used, and the drying temperature is -60℃ ~ -80℃.

6. A method for preparing two-dimensional flaky CrF3·3H2O micro-nano powder from the spherical CrF3·3H2O micro-nano powder according to claim 1, characterized in that: The spherical CrF3·3H2O micro-nano powder was ultrasonically treated in an ethanol solution to fully expand it to form a two-dimensional flaky CrF3·3H2O micro-nano powder material.

7. A method for converting CrF3·3H2O micro-nano powder into an amorphous state according to claim 1 or 6, characterized in that: The spherical or two-dimensional flaky CrF3·3H2O micro-nano powder is heat-treated at a temperature of 160-300°C for a time of more than 30 minutes to remove crystal water and obtain amorphous spherical or flaky CrF3 powder.

8. A method for converting CrF3·3H2O micro-nano powder into an amorphous state according to claim 1 or 6, characterized in that: The spherical or two-dimensional flaky CrF3·3H2O nanopowders are heat treated in an oxygen-deficient environment at a temperature of 400°C to 1000°C for more than 30 minutes to form Cr2O with oxygen vacancies. 2.4 Spherical or flake materials; The spherical or two-dimensional flaky CrF3·3H2O micro-nano powder is heat-treated in an atmospheric environment at a temperature of 400°C to 1000°C for a time greater than 30 minutes to form a spherical or flaky material of Cr2O3 with oxygen vacancies.

Citation Information

Patent Citations

  • Preparation method of yolk-shell-structured CrF3.3H2O

    CN107529519A

Cited By

  • Preparation method and crystalline state transformation method for spherical and sheet-like CRF 33h 2o micro-nano powder

    WO2026081430A1